I-search, you search, we all learn to research a how-to-do-it manual for teaching elementary school students to solve information problems - Duncan, Donna (How-to-do-it manuals for libraries, 2000)
"This manual introduces teachers and librarians to strategies to get students to move away from traditional research in which they merely restate information to a higher order of thinking. . . . Along the way, they will learn about choosing topics, evaluating sources, note taking, presenting findings, and working with peers to develop better skills."--SLJ.